Effects of monomer size on polymer mass transport at a crystalline interface. (11th December 2017) - Cadilhe, Antonio; Coura, P Z; Costa, B V
Abstract: The relevance of surface structure to polymer diffusion was considered in a few cases. In this work extensive Monte Carlo simulations are done to study the diffusion of a polymer on a crystalline surface. We study models for which we vary the monomer size, thus, allowing us to define a parameter γ as the ratio of the equilibrium distances between monomers to substrate particles. Physically, distinct γ values represent different materials. Two different models are considered: one (Model A ) where the equilibrium distance between monomers and substrate particles remains constant as we vary the size of the monomers and another (Model B ) where this distance scales with the monomer-monomer equilibrium distance. In Model A the monomer-monomer and monomer-substrate interactions have different ranges, which makes it anisotropic, while in Model B these ranges are the same, which makes it isotropic. Our results for Model A show that the presence of the crystalline substrate significantly affects the diffusion coefficient introducing an oscillation in the diffusion coefficient that depends on the ratio monomer size to lattice spacing ( γ ). When γ is a multiple integer of some lattice vectors the diffusion constant diminishes dramatically suggesting that the monomers settle. In Model B monomers do settle for γ = 5, but otherwise the behavior of the diffusion coefficient stays monotonic. Additionally, this model shows that larger γ values give similar diffusion coefficients, which might be of use to experimentalists.